Inferno - Brown, Dan, 1964- (Corgi Books, 2014)
Florence: Harvard symbologist Robert Langdon awakes in a hospital bed with no recollection of where he is or how he got there. Nor can he explain the origin of the macabre object that is found hidden in his belongings...